Sure, i'll join your cult eaudiobook A memoir of mental illness and the quest to belong anywhere. - Bamford, Maria (Simon & Schuster Audio, 2023)
From "weird, scary, ingenious" ( The New York Times ) stand-up comedian Maria Bamford, an instant New York Times bestselling, brutally honest, and "laugh-out-loud funny" (Jennette McCurdy, #1 New York Times bestselling author) memoir about show business, mental health, and the comfort of rigid belief systems—from Dale Carnegie's Ho w to Win Friends and Influence People, to Richard Simmons, to 12-step programs. Maria Bamford is a comedian's comedian (an outsider among outsiders) and has forever fought to find a place to belong. From struggling with an eating disorder as a child of the 1980s, to navigating a career in the arts (and medical debt and psychiatric institutionalization), she has tried just about every method possible to not only be a part of the world, but to want to be a part of it. In Bamford's "trademark blend of disarming intimacy and dark whimsy" ( Publishers Weekly ), Sure, I'll Join Your Cult brings us on a quest to participate in something . With sincerity and transparency, she recounts every anonymous fellowship she has joined (including but not limited to: Debtors Anonymous, Sex and Love Addicts Anonymous, and Overeaters Anonymous), every hypomanic episode (from worrying about selling out under capitalism to enforcing union rules on her Netflix TV show set to protect her health), and every easy 1-to-3-step recipe for fudge in between. Packed with "Bamford's brilliance, relentless humor, and insatiable instinct for survival ( Library Journal ), this memoir explores what it means to keep going, and to be a member of society (or any group she's invited to) despite not being very good at it. In turn, she hopes to transform isolating experiences into comedy that will make you feel less alone (without turning into a cult following).